Management and bioremediation of hydrocarbon-polluted soils in Antarctica - Ruberto, Lucas Adolfo Mauro (2020)
Until a few years ago, the Antarctic continent was considered a pristine place. However, human activity there changed that condition, being hydrocarbon pollution a concerning and attention-drawing issue. Soils around scientific stations show different levels of pollution caused by oil-derived fuels, such as gasoil. Bioremediation is a tested, effective technique to remove contaminating hydrocarbon from the soil. Biostimulated biopiles is the most effective, tested strategy for Antarctic soils that makes use of the microorganisms’ catabolic potential; ecopiles, in turn, seem to be a better alternative that brings more complex biological systems into the process, such as vascular plants, in order to obtain higher removal levels. Finally, a reflection is made that appropriate, specific logistics are needed to reduce execution times of these innovative bioremediation treatments.